Developing digital information literacy of parents on children’s health issues: Assessment based on the number of children in the family - Irina Yuryevna Pushkareva; Kseniya Sergeevna Tolstova; Nikolay Vladimirovich Kanygin; Olga Vladimirovna Lukasheva; Olga Alexandrovna Latukha (Science for Education Today, 2026)
Introduction. The article presents the results of a study of the problem of educating modern parents on children’s health issues as the basis for personalizing digital sanitary and educational work. The purpose of the study is to identify the specifics of developing digital information literacy of parents on child health issues based on its assessment depending on the number of children in the family. Materials and Methods. A sociological study was conducted among 138 parents visiting the polyclinic. The respondents were asked to indicate the number of children in the family and choose the most interesting topics related to children’s health. Results. The article presents the results of an empirical study of the priority directions of developing parents’ information literacy. It is noted that in the context of digitalization of healthcare, parents receive a significant amount of information about children’s health from various sources, including websites of medical organizations, social networks, messengers, mobile applications and other digital channels. Differences in the structure of parents’ information requests have been established depending on the number of children in the family. Parents with one child are more interested in issues of child development, nutrition and vitamins; parents with three or more children are more interested in issues of disease prevention, prevention of colds, allergies and other areas of preventive work. The data obtained can be used in planning sanitary and educational work of both medical and educational settings, the preparation of thematic materials, including for digital communication channels and the formation of parents’ information literacy on children’s health. Conclusions. Based on the analysis of the results of empirical research, it is concluded that the effectiveness of sanitary and educational work depends not only on the availability of information, but also on its compliance with the real information needs of parents.